INVESTIGATION OF THE CAUSES AND TYPES OF SPEECH PATHOLOGIES IN CHILDREN (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the causes and classifications of speech disorders in children. Specialists have identified multiple factors contributing to delayed or impaired speech development. Speech comprehension is essential for children’s cognitive, emotional, and social development. The study focuses on teaching methods, conditions that facilitate communication, and pedagogical technologies aimed at addressing these challenges.